Separação sólido-líquido em hidrociclones otimizados empregando sistemas concentrados e fluido não newtoniano - Gonçalves, Suélen Mara (2019)
Hydrocyclones are used to separate solid-liquid suspensions by centrifugal sedimentation. Due to its operational simplicity, small size, low maintenance and acquisition costs, its use is widespread in the petrochemical, mineral, food industry and other sectors. The geometry of hydrocyclones has a fundamental influence on separation performance as well as on-site operating conditions such as pressure drop, percentage of solids in the feed and fluid rheology. The optimization of the hydrocyclones operation is part of a scenario in which operating conditions are increasingly unfavorable and the search for improvements in processes to reduce operating costs and minimize effluent production is constant. In this context, the purpose of this work is to evaluate the performance of optimal hydrocyclone geometries, proposed by researchers from the Chemical Engineering Faculty at the Federal University of Uberlândia, operating with pseudoplastic fluids containing up to 10.0% of solids by volume. Carboxymethylcellulose (CMC) was used as a rheological modulator at concentrations ranging from 0.2% to 1.0% by weight. The effect of solids concentration, the addition of CMC, the underflow diameter, the vortex finder length and the pressure drop were investigated in the performance of the MAX, HOT, HGOT1 and HGOT3 hydrocyclones through a Central Composite Design. The increasing of the suspension’s apparent viscosity was found to severely impair hydrocyclone separation performance and to decrease the Euler number, due to a reduction in the intensity of rotational fluid movement. By modifying the fluid behavior index, n, from 0.99 to 0.48, the Total Efficiency of the MAX, HOT, HGOT1 and HGOT3 hydrocyclones decreased by 28%, 43%, 24% and 41%, respectively. The HGOT1 hydrocyclone showed promising results when working with diluted suspensions (η = 58%). The MAX and HGOT3 hydrocyclones presented similar thickening performances when operated with CCMC = 0.2%w. and CVA = 5.5%. The HOT showed intermediate performance when compared to other hydrocyclones. Finally, the performance equations of the MAX, HOT, HGOT1 and HGOT3 hydrocyclones were obtained and presented satisfactory fit. It was possible to evaluate hydrocyclones by working under conditions close to the ones observed in solid control systems, used in oil and gas drilling rigs.